Novostavba rodinného domu - Tyrlik, Radim (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Abstrakt Předmětem této bakalářské práce je zpracování stavebně technické části projektové dokumentace pro realizaci novostavby rodinného domu v Třinci, Oldřichovice, parc č. 3330/2. Stavba je umístěna v obci Třinec , v řídce zastavěném území a bude obklopena zástavbou ze severní a východní strany. Podél jižní a západní části pozemku se nachází místní pozemní komunikace (Č.P. 3340/5) široká 6 m. Na severní straně je nezastavěná parcela (Č.P. 3344/4) a parcela (Č.P. 161). Na severovýchodě je zastavěný pozemek s rodinným domem (Č.P. 65/1). Stavbu tvoří jedna budova, nebude se dělit na objekty. Dům je půdorysu tvaru symetrického L a je částečně podsklepen. Svislé nosné zdivo tvoří Vápenopískové tvárnice Silka S12-1800 10 DF, (tl.300 mm), suterénní zdivo je ze stejného materiálu jako nadzemní podlaží. Příčky jsou z Vápenopískových tvárnic Silka S20-2000 5 DF. Strop je proveden prefamonolitický, montovaný strop Porotherm se stropními trámy a vložkami. Střechu nese konstrukce krovu s dřevěnými a ocelovými prvky. Budova bude založena na základových pásech, jednoduché základové poměry. Parcela se nachází v kopcovitém terénu převýšení celého pozemku činí 6 m. Zastřešení tvoří valbová střecha se sklonem 35°. Podzemní voda se nachází 8,9 m pod úrovní stávajícího terénu. Nebude tedy ovlivňovat stavbu. Objemová aktivita radonu 1.NÍZKÝ STUPEŇ

Abstract The subject of this thesis is the process of building technical part of the project documentation for the realization of a new family house in Třinec, Oldřichovice, parcel number. 3330/2. The building is located in the village of Třinec, in sparsely built-up area and will be surrounded by buildings from the north and east sides. Along the southern and western parts of the property there is a local road (N.P. 3340/5) which is 6 meters wide. On the north side is undeveloped parcel (N.P. 3344/4) and parcel (N.P. 161). In the northeast, there is a built family house with land (N.P. 65/1). The construction is formed by one building and it will not be splitted into other objects. The house has symmetrical L-shaped floor plan and it has got a partial basement. Vertical load-bearing masonry is made of Calcium silicate molded bricks Silka S12-1800 10 DF, (thickness 300 mm), basement walls are made of the same material as the aboveground storay. Partition walls are made of calcium silicite moped bricks Silka S20-2000 5 DF. The ceiling is made as monolithic-prefabricated, mounted ceiling Porotherm with ceiling beams and bars. The roof holding is supported by truss structure with wood and steel components. The building will be based on the foundation strips, simple foundation ratios. The parcel is situated in hilly terrain, vertical rise of the terrain is 6 meters. Roofing is made by a hipped roof with a slope of 35 °. Groundwater is located 8.9 m below the existing ground. It will therefore not affect the construction. The volume activity of radon 1.LOW DEGREE
Detached house
Keywords: Klíčová slova: Stavba; rodinný dům; půdorys; řez; projekt; pozemek; vápenopískové tvárnice.; Keywords: The building; family house; floor plan; sectional view; project; land; calcium silicate molded bricks.